KESIAPAN DAN PENGUATAN KELEMBAGAAN MASYARAKAT DALAM MENDUKUNG PENGELOLAAN PROGRAM RESTOCKING LOBSTER - Zahri Nasution; Bayu Vita Indah Yanti; Nurlaili Nurlaili (Jurnal Kebijakan Perikanan Indonesia, 2018)
Pemulihan populasi lobster dilihat dari aspek sosial ekonomi adalah penyiapan rekayasa sosial dalam mendukung upaya penguatan kelembagaan restocking lobster berbasis masyarakat. Penelitian ini bertujuan untuk mengevaluasi kesiapan dan penguatan kelembagaan masyarakat dalam pengelolaan program restocking lobster untuk meningkatkan kesejahteraan masyarakat. Penelitian dilakukan pada tahun 2015 di Nusa Tenggara Barat (Kab. Lombok Tengah dan Kab. Lombok Timur), Jawa Barat (Kab. Pangandaran) dan Banten (Kab. Pandeglang). Data aspek kelembagaan yang dikumpulkan adalah kegiatan pemanfaatan dan pengelolaan sumberdaya perikanan kaitannya dengan pengembangan restocking lobster. Informan terdiri dari masyarakat nelayan, petugas pemerintah daerah di berbagai kantor dinas terkait, petugas di kantor Desa, dan informan yang dianggap mengetahui keberadaan data dan informasi kelembagaan pengelolaan sumberdaya perikanan di wilayah yang diteliti. Wawancara dilakukan secara terstruktur dan tidak terstruktur yang dipandu dengan topik data. Data dianalisis menggunakan metode kualitatif. Hasil kajian menunjukkan bahwa lokasi yang paling memiliki kesiapan dalam mendukung program restocking lobster adalah Kabupaten Pangandaran., maka Opsi kebijakan yang diperlukan dalam rangka meningkatkan kinerja program restocking lobster berbasis masyarakat adalah memberikan pemahaman kepada pengurus organisasi yang terbentuk dalam program restocking lobster dan manfaatnya bagi masyarakat, sumber daya dan populasi lobster dan pemerintah. Termasuk didalamnya regulasi penangkapan dan dukungan sarana dan prasarana untuk kelancaran petugas pengawasan di lapangan. Penegakan aturan yang terkait dengan penetapan otoritas pengelolaan sumberdaya lobster terkait program restocking lobster perlu dilakukan.Lobster population recovery, viewed from the social and economic aspects will require the preparation of social engineering in support of the efforts to strengthen community-based lobster restocking. This study was conducted to express readiness and institutional strengthening in the community in the management of lobster restocking program, with the ultimate goal is to improve the welfare of society. The study was conducted in 2015 with the location of West Nusa Tenggara (in Central Lombok district and East Lombok), West Java (in Pangandaran district), and Banten (in the Pandeglang district). The data collected related to the institutional aspects is the activity of resource utilization and management of fisheries and fisheries-based connection with the development of restocking activities. Informants consisted of fishing communities, local government officials in the various offices concerned, the clerk in the office of the chief, and informants were considered to know the existence of data and information on fisheries resources management institutions in the regions studied. Interviews were conducted either in a structured or unstructured guided by the topic of data prepared in this study. Data were analyzed using qualitative methods. The results showed that most locations have the readiness to support the restocking program is Pangandaran Regency. In order to improve the performance of community-based lobster restocking programs, the policy options required are to provide an understanding to the organizational board formed in the lobster restocking program and its benefits to communities, resources and government. Including the restrictions on the use of fishing gear and support facilities and infrastructure that provide fluency in the duty as a supervisory officer in the field. It is also necessary to enforce the rules related to the establishment of fish / lobster resource management authority related to the lobster restocking program.